ASSOCIATION OF THE NUMBER OF COMPONENTS OF THE MEATBOLIC SYNDROME AND CAROTID ARTERY DISEASE - Deleva Stoshevska, Tatjana; Nikoloska, Sofija; Nikoloski, Marko; Stoshevski, Bojan; Veljanovski, Dimitar (Journal of Morphological Sciences; Vol 4 No 2 (2021): JMS, 2021)
Metabolic syndrome (MetS) is a group of at least three of the following metabolic disorders: central obesity, elevated glycaemia, high serum triglycerides, low serum high-density lipoprotein (HDL), and high blood pressure. Carotid artery disease (CAD) involves changes in the arterial wall that cause thickening of the intima-media (IMT), narrowing, or complete obstruction of the carotid artery lumen. Objective:To determine the impact of the number of MetS components on CAD. This analytical unicenteric cross-sectional study included 80 subjects with MetS according to the National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP III) criteria. CAD was diagnosed with the Esaote My Lab70 HVG device, with a linear probe (7.5 MHz), according to the Ultrasound consensus criteria for CAD of the Association of Radiologists (2002, San Francisco). 34 subjects (42.5%) had 4 components of MetS, 24 subjects (30%) had 3 components, 22 subjects (27.5%) had 5 components. Gender and age have no statistically significant effect on the influence of metabolic risk factor as components of MetS (p = 0.38, p = 0.72, respectively). CAD was diagnosed in 77 subjects (96.25%), in 21 subject (87.5%) with 3 components of MetS and in all subjects with 4 and 5 components of MetS.This statistically confirmed that subjects with a smaller number of MetS components significantly have less CAD (p = 0.026). The increase in the number of components and the synergistic effect of individual MetS components is significantly associated with CAD. Keywords : metabolic syndrome, carotid artery disease https://doi.org/10.55302/JMS2142180ds